ACC Interviews: Prof Dr Yacouba Banhoro & Prof Dr Désire Boniface Somé Université Joseph Ki-Zerbo (African Cluster Centres, 2019)
Interview with Prof Dr Yacouba Banhoro & Prof Dr Désire Boniface Somé from our African Cluster Center Université Joseph Ki-Zerbo in Ouagadougou, Burkina Faso